Serotipificación y detección genética de Salmonella spp de origen aviar - Huarcaya R., Freshia (2022)
The aim of this study was to molecularly and serologically identify Salmonella spp present in isolates from avian eggs, carcasses, and viscera. In total, 46 isolates of avian origin identified as Salmonella spp were evaluated through cultures and biochemical tests in the period 2012-2017 from various districts of Lima. These isolates are kept in the Bacteriology Laboratory stock of the Universidad Nacional Mayor de San Marcos. The strains were reactivated, and suspicious Salmonella spp colonies were reconfirmed by culturing on selective media. Subsequently, the PCR was performed on the suspicious samples as a method of genetic diagnosis of Salmonella. The invasiveness gene invA, a gene involved with the virulence of Salmonella, was detected. Serotyping was performed with polyvalent and monovalent antisera for serogroup and serovar in the Enteropathogens Laboratory of the National Institute of Health (INS), and finally the serovars were determined according to the scheme proposed by Kauffmann-White. The 46 strains showed molecular weight bands corresponding to the invA gene (244 bp). All strains were identified by serotyping, obtaining S. Infantis (34.8%), S. Pullorum (34.8%), S. Gallinarum (15.2%), S. Enteritidis (8.7%) and S. Typhimurium (6.5%). The results reveal the predominance of circulating serovars in avian samples, as well as their implication in public health.